2021
DOI: 10.3390/healthcare9121723
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in the Time of COVID-19: Affections and Impacts among the Spanish Primary Care Workforce

Abstract: Background: The literature review shows that most studies on the psychological impact of COVID-19 on healthcare professionals have focused on hospital staff, with few specifically addressing the primary care workforce. This study aims to explore primary care workers’ verbal accounts of the emotions they experienced. Methods: This is a qualitative study carried out between July and December 2020 in Spain. Semi-structured interviews and focus groups were conducted with primary care workers. Data were analysed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Families were their primary source of support in vulnerable situations, protecting them from or cushioning them against the psychological impact of the pandemic (18,49). Similarly, Pulido-Fuentes et al (50) demonstrated the critical role of primary care family and community health services in protecting emotional health and maintaining mental health, even among direct care workers. Family and friends' support and positive attitudes have been shown to reduce perceived stress and be more supportive during infectious disease outbreaks (16).…”
Section: Discussionmentioning
confidence: 99%
“…Families were their primary source of support in vulnerable situations, protecting them from or cushioning them against the psychological impact of the pandemic (18,49). Similarly, Pulido-Fuentes et al (50) demonstrated the critical role of primary care family and community health services in protecting emotional health and maintaining mental health, even among direct care workers. Family and friends' support and positive attitudes have been shown to reduce perceived stress and be more supportive during infectious disease outbreaks (16).…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that the data are discouraging but even more so if we observe the diagnosed cases of healthcare personnel [ 7 ]. Studies on the impact of the pandemic on health workers in the Spanish context have shown a high prevalence of emotional and general health symptoms [ 8 , 9 ]. In the region of Murcia, to date, 331,577 confirmed cases of COVID-19 have been registered.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the crisis caused by the SARS-CoV-2 virus has only accelerated already existing processes and dynamics, affecting the working conditions of healthcare professionals worldwide. In particular, making decisions against their professional ethical standards and witnessing the unequal distribution of healthcare resources among the population caused an added moral strain [ 60 ].…”
Section: Discussionmentioning
confidence: 99%